Post-war reconstruction documents - TUC Congress, 1945 (1945)
1945 1945-1960 "Post-war reconstruction documents - TUC Congress, 1945" [HFR0138], 1945 Four key reports on post war policies were published at the 1945 TUC Congress. These covered taxation reform, public ownership of transport services, the financial aspects of the transfer of industries from private to public ownership and the regulation of monopolies and large companies.